In silico and In vitro Antibacterial Activity of Centella asiatica Leaves Bioactive Compounds Against Aquaculture Pathogenic Bacteria - Andriyanto, Septyan; Maftuch, Maftuch; Andayani, Sri; Nafiqoh, Nunak; Gardenia, Lila; Novita, Hessy; Nursid, Muhammad (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research The GC-MS analysis of the asiatica leaves extracts identified 53 bioactive compounds. The crude extracts of asiatica showed antibacterial efficacy against fish pathogenic bacteria. 13-Hexyloxacyclotridec-10-en-2-one has the potential to be an inhibitor of DNA gyrase. Bioactive compounds derived from C. asiatica leaves extracts show potential as antibacterial agents. Abstract Antimicrobial agents are crucial for managing bacterial infections in fish cultures. Centella asiatica is a medicinal plant recognised for its diverse bioactive compounds with important antibacterial properties. The present study aimed to investigate the antibacterial activity of C. asiatica leaves bioactive compounds on fish pathogenic bacteria using an in vitro and in silico approach. The maceration method was used to extract bioactive compounds from C. asiatica leaves and was identified using Gas Chromatography-Mass Spectrometry (GC-MS). In vitro analysis of antibacterial activity was evaluated using the minimum inhibitory concentration method. While in silico molecular docking is applied alongside assessing Lipinski's rules of five, as well as absorption, distribution, metabolism, excretion, and toxicity properties. The result of the GC-MS examination of the C. asiatica leaf extracts identified 53 bioactive compounds. In vitro studies showed antibacterial efficacy of leaf extracts against fish pathogenic bacteria (Streptococcus agalactiae, Bacillus subtilis, and Staphylococcus aureus) with minimum inhibitory concentration values of 12,5 mg/ml. In silico molecular docking analysis showed that several bioactive compounds have the potential to be DNA gyrase inhibitors. Compound 13-Hexyloxacyclotridec-10-en-2-one has the highest inhibition with binding energy of −7,4 Kcal/mol compared to ciprofloxacin as drug standard with a binding energy value −7,3 Kcal/mol. The following compound is gamma.-Muurolene (−6,7 Kcal/mol), Copaene (−6,6 Kcal/mol) and Humulene (−6,6 Kcal/mol). These results suggest that bioactive compounds of C. asiatica leaves extracts hold promise as potential antibacterial agents for treating fish pathogenic bacteria infections.